High performance work systems and organizational performance: modeling the mediating role of managers' trust in employee representation systems in European organizations - Adhami, Tarek; Timur, Tarik (Emerald Group Publishing Ltd, 2025)
PurposeThis paper aims to examine the impact of managers' trust in employee representation systems on the relation between HPWS and organizational performance. The present research, by including the trust of managers in ER, studies managers as direct factors that affect the HPWS-performance relation.Design/methodology/approachThe study employed partial least square structural equation modeling (PLS-SEM) through SmartPLS software using a formative model (Mode B) that includes mediation on data collected by Eurofound from 6,980 establishments in 29 European countries.FindingsOur findings show that HPWS has positive direct effects on organizational performance. Our results indicate that trust of managers in ER has a mediator role and has a positive effect on the HPWS-performance relation.Originality/valueThe present study may be the first study that directly incorporates the role of managers and managers' trust in the employee representation system in the relation between HPWS and organizational performance, highlighting the importance of the managers in the organization and emphasizing their role in the HPWS-performance relation.
Keywords: HPWS; Organizational performance; Employee representation; Managers' trust